Effectiveness of diabetes conversation Map™ on insulin acceptance among insulin refusal patients of type 2 diabetes mellitus - Tahir, Nur Shaharni Mohd (2018)
Background: Diabetes education is a very crucial aspect of management for a diabetic patient. Educations can be delivered either by group or individual. For busy health centres, group education is the most practical approach in the setting. However, in most of the public hospital setting, the group-based diabetes education is still not yet well established. In recent years, group-based diabetes education using the diabetes conversation maps (DCM) endorsed by the International Diabetes Federation has been popularised ever since the complete set was translated into malay language. However, the effectiveness of this diabetes conversation map is still not known in our country. Objectives: To compare the percentage of insulin acceptance between the intervention group (those who receive DCM education) and control group (those who receive standard counselling) and associated factors of insulin acceptance among uncontrolled type 2 diabetic patients, who refused insulin initiation attending Klinik Rawatan Keluarga HUSM. Methodology: An interventional study was carried out where a total of 88 Type 2 diabetic adults from Klinik Rawatan Keluarga, HUSM with glycosylated haemoglobin (HbA1c) concentrations of 8% and or more and refused insulin treatment were randomised into intervention(those who receive DCM education) and control groups(those who receive standard individual education). Post sessions, participants were reviewed by the investigator to find out their acceptance towards insulin initiation. Logistic regression was done to look at the factors associated with the insulin acceptance. Results: The response rate was 97.7%. There was a significant difference in insulin acceptance between the intervention group education using DCM as compared to the control group using standard individual education module (86% vs 11%, p < 0.001). There was a significant association between history of relatives use insulin and insulin acceptance (AOR: 6.96; 95% CI: 2.30, 21.03; p=0.001). Conclusion: Group education using Diabetes Conversation Map (DCM) is effective in increasing insulin acceptance among patient who initially refused insulin treatment. We recommend using DCM in primary care centres for diabetic patients who had difficulties in accepting insulin. Having relative that use insulin is a significant associated factor among patient who accepts insulin.